Vystuplenie prezidenta RF B.N. El'tsina na vstreche glav gosudarstv SNG . Vystuplenie prezidenta RF B.N. El'tsina na vstreche glav gosudarstv SNG . President of the Russian Federation B.N. Yeltsin's Speech at the CIS Leaders Meeting . Выступление президента РФ Б.Н. Ельцина на встрече глав государств СНГ - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Discussion of prospects for cooperation among CIS states. Featured in the program: Yeltsin, Boris Nikolayevich (President of the Russian Federation); Nazarbaev, Nursultan Abishevich (President of the Republic of Kazakhstan) О перспективах сотрудничества стран Государственный комитет по чрезвычайному положению (СНГ). В программе участвуют: Ельцин, Борис Николаевич (Президент Российской Федерации); Назарбаев, Нурсултан Абишевич (Президент Республики Казахстан)